INFLUENCE OF ALLOGENEIC FIBROBLASTS ON THE DYNAMICS CYTOLOGICAL PICTURE IN BURN WOUND - V. V. Soloshenko (Кубанский научный медицинский вестник, 2016)
The aim of the study was to investigate the influence of allogeneic fibroblasts on during wound healing process in burn wound on the basis of cytology data. Achieved smear prints of burn in 14 victims of explosions of methane-coal mixture, which were treated in the Donetsk burn center in the period from 2009 to 2012. In the surgical treatment of these patients with extensive burns used cell culture allogeneic fibroblasts. It was found that the change of inflammatory type prints on the regenerator to the study site occurs at 7,14±0,61 days after escharectomy, the control - at 11,79±0,62 per day. Through the use of allogeneic fibroblasts after the escharectomy with deep dermal burns were able to prepare a wound to skin grafting 1,65 times faster when compared to standard methods of postoperative management of burn wounds.